Performing the Post-Anthropocene AI: When a Robot Writes a Play - BAŞ, ANIL (My University, 2023)
Promoted as the first theatrical play written by artificial intelligence, AI: Když Robot Pí še Hru (AI: When a Robot Writes a Play) premiered and livestreamed globally on 26 February 2021.1 The script is a series of dialogues generated in English by OpenAI’s language model GPT-2 (Radford et al. 2019). It was then translated into Czech and performed in Prague, though not initially to a live audience.2 In total, 92% of the characters’ lines are computer-generated (THEaiTRobot 1.0 et al.2021). THEaiTRE, a team of natural language processing and theatre researchers, initiated the project to celebrate the centenary of the term robot coined by Czech playwright Karel Čapek in 1921 in R.U.R. (Rossum’s Universal Robots). In Čapek’s play, engineers produce artificial humanoids for cheap labor, but the robots rebel. In the play’s climactic moment, the character Radius—buttressed by the humanoids’ newly gained status as conscious beings—signals the end of humankind: “Robots of the world! The power of man has fallen. A new world has arisen: The Rule of the Robots! March!” (Čapek [1921] 1923:165). Nicholas Anderson reads R.U.R. as a potent critique of humanism, finding constitutive possibilities in human extinction (2014). According to Jana Horáková and Jozef Kelemen, the play significantly repositions humans alongside and entwined with machines in a complex new world (2011). Chiara Mengozzi convincingly argues that Čapek spurs us to look beyond anthropocentrism (2020) while Micha Braun examines the post-anthropocentric possibilities exemplified in theatrical projects from Central Eastern Europe (2022).
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Sanat; Social Sciences and Humanities; Philology; Art; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; EDEBİYAT; SANAT; Arts & Humanities (AHCI); ARTS & HUMANITIES; LITERATURE; ART; Görsel Sanatlar ve Gösteri Sanatları; Sosyal Bilimler ve Beşeri Bilimler; Edebiyat ve Edebiyat Teorisi; Visual Arts and Performing Arts; Social Sciences & Humanities; Literature and Literary Theory